Intervertebral Disc Characteristic on Progressive Neurological Deficit - Farid Yudoyono; Rully Hanafi Dahlan; Muhammad Zafrullah Arifin (International Journal of Integrated Health Sciences, 2017)
Objective: To examine the intervertebral disc characteristic on magnetic resonance imaging (MRI) in lumbar herniated disc (LHD) patients with progressive neurological deficit.Methods: Patients were collected retrospectively from Dr. Hasan Sadikin General Hospital Database from 2011–2013 with LHD, had neurological deficit such as radiculopathy and cauda equine syndrome for less than four weeks with a positive sign confirmed by neurological examination and confirmatory with MRI examination.Results: A total of 14 patients with lumbar herniated disc disease (10 males, 4 females) suffered from progressive neurological deficit with an average age of (52.07±10.9) years old. Early disc height was 9.38±0.5 mm and progressive neurological deficit state disc height was 4.03±0.53 mm, which were significantly different statisticaly (p<0.01). Symptoms of radiculopathy were seen in 11 patients and cauda equine syndrome in three patients. Modic changes grade 1 was found in five patients, grade 2 in eight patients,grade 3 in one patient, Pfirmman grade 2 in eleven patients and grade 3 in three patients. Thecal sac compression 1/3 compression was seen in four patients and 2/3 compression in ten patients.Conclusions: Neurosurgeon should raise concerns on the characteristic changes of intervertebral disc in magnetic resonance imaging examination to avoid further neural injury in lumbar herniated disc patients.Keywords: Lumbar herniated disc, magnetic resonance imaging, progressive neurological deficit DOI: 10.15850/ijihs.v5n2.1042